STRUCTURAL BEHAVIOR OF HYBRID REINFORCED CONCRETE COUPLED BEAMS CONTAINING REACTIVE POWDER CONCRETE AND HIGH STRENGTH CONCRETE - A. Sabit, Hiba; N. Abbas, Aamer (Journal of Engineering and Sustainable Development, 2021)
Reactive powder concrete and high strength concrete have superior mechanical and structural properties, however, the major drawback of this new construction material is its high cost compared to traditional concrete. This study presents an experimental investigation on the structural behavior of hybrid rectangular cross section (coupled) reinforced concrete beams poured with normal and high strength concrete (HSC) at compression chord, normal strength concrete (NSC) at ribs, and reactive powder concrete (RPC) at tension chord. The experimental work consists of pouring and testing four specimens with dimensions (1100mm length, 100 mm width, and 400 mm height). First specimen, rectangular solid normal concrete beam for comparison with specimens, second specimen, coupled beam poured with normal strength concrete at top chord, and two other specimens of coupled beams cast with high strength concrete with two compressive strengths (50 MPa and 70 MPa) at top chord. The effect of top chord concrete type at each specimen on ultimate load capacity, energy absorption, deflection and cracking load are studied in this investigation. Experimental results showed that the ultimate load carrying capacity and energy absorption increased to 76.9 % and 108.33 % respectively, compared with the solid specimen and recorded a reduction in deflection values through loading life and cracking load when using higher compressive strength of high strength concrete in compression chord in addition to reactive powder concrete in tension zone.